Corona pandemic in the sociology of daily life in urban settings - Mabrouki, Amar (Journal of Human Sciences, 2021)
This study aims to reveal the invisible side of people's daily practices in the face of the “Coronavirus Covid19” Pandemic that Algeria isexperiencing. Thus the degree of awareness of individuals of the severity of this epidemic. It is also about detecting the fragility of social relations in an urban environment. using a sociological approach, For this, we have adopted a descriptive approach based on general observation and by sending an electronic questionnaire intended for random cross-sectional samples. we have achieved the most important results are: -The dominance of the social scene by informal media-Negligent behavior with this crisis ، and this is due to the lack of a health culture in terms of prevention and 'unconsciousness - the use of food storage, which is due to individualism and selfishness values.